CULINARY (Get to Know Hypertension Control Education Efforts): Education and mentoring for hypertension prevention in risk groups - Usman, Suharno; Lampus, Nancy Sicilia; Nurmansyah, Muhamad (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: The high prevalence of hypertension in Indonesia has a major economic impact, thus requiring improved planning and implementation of effective hypertension management.Methods: This study aims to evaluate activities in the Community Partnership Program (CPP) or cadres consisting of briefing and educational training for the mentoring team/cadres (partners) and the practice of a healthy food menu in the form of a low-salt diet. In addition, this CPP activity also measures participants' blood pressure using a sphygmomanometer and stethoscope and the participant's knowledge scale (pre and post-test) about hypertension using the Indonesian version of the Hypertension Knowledge-Level Scale (HK-LS) questionnaire.Results. The study discovered a significant correlation (ρ.033) between the use of low-salt food management skills and literacy levels about hypertension before and after health education. Pre-post measurements of diastolic blood pressure (ρ.002) and systolic blood pressure (ρ.045). Increasing their understanding of the importance of health education about healthy food according to diet for chronic diseases.Conclusion. The community partnership program-cadres significantly enhanced participants' knowledge of food choices, health education, hypertension management, and cooking techniques, emphasizing the importance of educational interventions in improving long-term health outcomes.